Preparation of Boron Suboxide Nanoparticles and Their Processing - Jānis GRABIS; Dzintra RAŠMANE; Aija KRŪMIŅA; Aloizijs PATMALNIEKS (Medžiagotyra, 2012)
Crystalline boron suboxide B6O particles with size in the range of 1.5 µm – 2 µm and crystallite size in the range of 32 nm – 40 nm were prepared by calcination at 1400 °C for one or two hours of precursors obtained by mixing X-ray amorphous boron with water solution of B2O3 followed by evaporation and drying. Decrease of molar ratio B/B2O3 from 16 to 14 in the precursor mixture reduced nonstoichiometry of prepared B6O although simultaneously it increased admixture of B2O3. Particulate composites of B6O with TiN or Ni nanoparticles were prepared by mechanical mixing. The spark plasma sintering process intensified the densification of prepared boron suboxide nanoparticles at 1900 °C and allowed manufacturing of fully dense bodies (98 %) during five minutes. Additives of TiN or Ni nanoparticles reduced sintering temperature to 1700 °C and their promoted formation of Ti or Ni borides. DOI: http://dx.doi.org/10.5755/j01.ms.18.1.1345